Marriage satisfaction is associated with the incidence of perinatal depression - Pinem, Lina Herida; Bin Sansuwito, Tukimin; Nambiar, Nisha (Holistic Nursing Plus, 2025)
Introduction: Marital satisfaction, which includes aspects of communication, emotional intimacy, partner support, and quality of interaction, is believed to play an important role in maternal mental health after childbirth. This dissatisfaction can increase feelings of loneliness, stress, and anxiety, all of which can worsen the mental state of the postpartum mother. Women who experience dissatisfaction in their marital relationships have a higher tendency to experience postpartum depression. The prevalence of depressive disorders in the world population is 3-8% with 50% of cases occurring at the productive age of 20-50 years. World Health Organization. (WHO) states that depressive disorder affects 20% of women and 12% of men at some point in life. Objective: To find out if there is a relationship between marital satisfaction and the incidence of postpartum depression in East Bekasi. Methods: This study is an analytical study, meaning a study that aims to see the relationship or influence in the form of analytical descriptive research with a crossectional approach using the chisquere test, Research results: the results of the Chi-Square Statistical Test obtained a p-Value of 0.043 (p-value <0.05) so that Ha was accepted by Ho and rejected which means that there is a meaningful relationship between marital satisfaction and depression in postpartum mothers. Bottom Line: Women who are dissatisfied with their marriage are more at risk of postpartum depression. These findings are in line with many previous studies that show that the quality of a marital relationship can affect a mother's mental well-being after childbirth. Therefore, it is important to pay attention to the aspect of marital satisfaction as part of efforts to prevent postpartum depression.